Telescoped, Divergent, Chemoselective C1 and C1‐C1 Homologation of Imine Surrogates: Access to Quaternary Chloro‐ and Halomethyl‐Trifluoromethyl Aziridines. (25th January 2019) - Ielo, Laura; Touqeer, Saad; Roller, Alexander; Langer, Thierry; Holzer, Wolfgang; Pace, Vittorio
Abstract: A conceptually novel, high‐yielding, mono‐ or bis‐homologation was realized with lithium halocarbenoids and enables the one‐step, fully chemocontrolled assembly of a new class of quaternary trifluoromethyl aziridines. Trifluoroacetimidoyl chlorides (TFAICs) act as convenient electrophilic platforms, enabling the addition of either one or two homologating elements by simply controlling the stoichiometry of the process. Mechanistic studies highlighted that the homologation event, carried out with two different carbenoids (LiCH2 Cl and LiCH2 F), leads to fluoromethyl analogues in which the first nucleophile is employed for constructing the cycle and the second for decorating the resulting molecular architecture. Abstract : Mono‐ oder Dihomologisierung mit Lithium‐Halogencarbenoiden liefert Trifluormethylaziridine. Dabei dienen Trifluoracetimidoylchloride als elektrophile Plattformen für die Addition von einer oder zwei Homologisierungseinheiten. Mit zwei verschiedenen Carbenoiden entstehen Fluormethylanaloga, wobei das erste Nukleophil in den Ring eingebaut wird, während das zweite an diesen angehängt wird.